(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
This study was carried out on a model farm in Al-Sweira. The spatial distribution of physical and chemical soil characteristics and mapped using geostatistical method to ease the map exportation procedure in the geographic information system researches. Physical and chemical soil properties were measured. Distribution of soil particle sizes and some chemical characteristics (soil salinity, organic matter content, cation exchange capacity, carbonate mineral content, total nitrogen, above ground biomass), Clay content and Soil salinity showed high soil variation in comparison to other soil properties in the spatial distribution maps prepared using IDW method in ArcMap protocol, also, above ground biomass showed a relationship to land use where the more land used in agriculture, the highest biomass found in the upper horizon. Soil Organic Carbon and soil organic matter showed lower spatial variation due to the low component of them in soil. CEC has correlated to clay content distribution in the upper horizon of soil pedons, where it also showed high spatial variation in soil. Total nitrogen was measured and showed low and medium ranges of where spatial distribution explains the variability in this property. Using geotechniques is feasible to explain soil variability and spatial distribution of soil properties to explain soil forming factors and processes, hence, it is a suitable method to map soil properties and understand soil variability. Land suitability for grain crops was mapped for this farm, the most extensive suitability class was Class S3, moderate suitability.